Matrix Degradative Enzymes and Their Inhibitors during Annular Inflammation: Initial Step of Symptomatic Intervertebral Disc Degeneration - Kim, Joo Han; Park, Jin Hyun; Moon, Hong Joo; Kwon, Taek Hyun; Park, Youn Kwan (Journal of Korean Neurosurgical Society, 2014)
Symptomatic disc degeneration develops from inflammatory reactions in the annulus fibrosus (AF). Although inflammatory mediators during annular inflammation have been studied, the roles of matrix metalloproteinases (MMPs) and their inhibitors have not been fully elucidated. In this study, we evaluated the production of MMPs and tissue inhibitors of metalloproteinase (TIMPs) during annular inflammation using an in vitro co-culture system. We also examined the effect of notochordal cells on annular inflammation. Human AF (hAF) pellet was co-cultured for 48 hours with phorbol myristate acetate-stimulated macrophage-like THP-1 cells. hAF pellet and conditioned media (CM) from co-cultured cells were assayed for MMPs, TIMPs, and insulin-like growth factor (IGF)-1 levels using real-time reverse-transcriptase polymerase chain reaction and enzyem-linked immunosorbent assay. To evaluate whether notochordal cells affected MMPs or TIMPs production on annular inflammation, hAF co-cultured with notochordal cells from adult New Zealand White rabbits, were assayed. MMP-1, -3, -9; and TIMP-1 levels were significantly increased in CM of hAF co-cultured with macrophage-like cells compared with hAF alone, whereas TIMP-2 and IGF-1 levels were significantly decreased (p<0.05). After macrophage exposure, hAF produced significantly more MMP-1 and -3 and less TIMP-1 and -2. Interleukin-1β stimulation enhanced MMP-1 and -3 levels, and significantly diminished TIMP-2 levels. Co-culturing with rabbit notochordal cells did not significantly influence MMPs and TIMPs production or COL1A2 gene expression. Our results indicate that macrophage-like cells evoke annular degeneration through the regulation of major degradative enzymes and their inhibitors, produced by hAF, suggesting that the selective regulation of these enzymes provides future targets for symptomatic disc degeneration therapy.